MATERNAL RISK FACTORS ASSOCIATED WITH STUNTING AMONG UNDER-FIVE CHILDREN IN SOUTHEAST ASIA: A LITERATURE REVIEW - Anggraini, Anita Dewi; Windarena, Diyas; Rochmaniah, Dwi Ardani (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Stunting remains a major global health challenge, with a worldwide prevalence of 21.9% among children under five. The Southeast Asian region contributes more than one-quarter of all stunting cases globally. This condition affects not only the growth and development of children but also increases morbidity and mortality rates, which in turn influence national productivity and economic outcomes in the future. Maternal risk factors play a critical role, contributing more than 50% to a childâ€™s growth. This study aims to identify maternal risk factors associated with stunting in Southeast Asia. Data were retrieved from PubMed, Springer, and ProQuest using the keywords â€œchildren,â€ â€œstunting,â€ â€œmaternal risk factors,â€ and â€œSoutheast Asia.â€ Of the 768 articles identified, only 10 met the inclusion criteria. Most studies were conducted in Indonesia, followed by the Philippines, Myanmar, Cambodia, and Vietnam. Maternal factors associated with stunting include infections during pregnancy, nutritional status, maternal height, educational level, hygiene practices, supplement intake during pregnancy, maternal age, employment status, MUAC, dietary diversity during pregnancy, and maternal stress.